MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS MELALUI PENERAPAN STRATEGI REACT (Relating, Experiencing, Applying, Cooperating, And Transferring) PADA MATERI TEXT DESCRIPTIVE DI KELAS X 1 SMA NEGERI 10 PEKANBARU: Increasing English Learning Results through the React Strategy Application (Relating, Experiencing, Applying, Cooperating, and Transferring) on Descriptive Text in Class X 1 SMA Negeri 10 Pekanbaru - Rusli, Muhamad (Perspektif Pendidikan dan Keguruan, 2017)
Learning is a process by which a person undertakes to gain a whole new behavioral change, as a result of his own experience in interaction with the environment. Dimyati and Mudjiono also revealed that learning is a complex student behavior and behavior. As an action, learning is only experienced by the students themselves. A teacher must be able to define, select and apply appropriate learning strategies so as to solve existing learning problems and ultimately can achieve competence or learning objectives optimally.Strategy is a plan or steps that are carried out systematically that has a system to facilitate the implementation of activities to achieve the goals specified. Learning is only one-way oriented, students tend to rely on information from teachers only, the interaction between students in the discussion is still lacking so that student learning outcomes are less satisfactory.Based on the learning conditions need to be applied strategy that is able to build the learning process and can guide students to understand the concept of learning given the REACT strategy. The REACT strategy (Relating, Experiencing, Applying, Cooperating, and Transferring) is a contextual learning strategy consisting of five elements, namely relating, experiencing, applying, cooperating, and transferring Transfer). Based on the result of the research, the result of learning is increased from the first cycle, second cycle and third cycle respectively (73,61%), (80,00%) and (83,40%).